Akuntabilitas Pelayanan Publik Dalam Pembuatan E-KTP Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Timor Tengah Utara - Ammuni, Protus; Patiung, Marthen; Agustian, Dimas (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
The formulation of the problem in this study is How is the process and achievement of public service accountability in making E-KTP at the population and civil registration office of North Central Timor Regency. This study aims to analyze the process and achievement of public service accountability in making E-KTP at the population and civil registration office of North Central Timor District. This type of research uses descriptive qualitative research methods. The data sources used are informants and documents. Data collection techniques are carried out by conducting observations, interviews, qualitative data analysis models: Data reduction, data presentation, and conclusion drawing. The results of the study explain that legal accountability and honesty at the TTU district headquarters in the E-KTP making service have strictly complied with the operational standards (SOP) that have been set. Process accountability in making E-KTP at the dukcapil of TTU district has been clearly regulated and carried out in a structured manner, starting from requirements, registration, recording, to printing E-KTP. Program accountability at the TTU district dukcapil is the application of the queue number system, and in the E-KTP making service program has reached the national target of 98%. Policy accountability at the TTU district dukcapil is that all dukcapil employees have clear responsibilities ranging from responsibilities to local government to responsibilities to the community